Pelatihan dan Pengembangan Guru Sebagai Sumber Daya Manusia Bidang Pendidikan di Era Kecerdasan Buatan (AI) - Imam Taufik; Ida Rindaningsih (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
The development of Artificial Intelligence (AI) technology has brought significant transformation across various sectors, including education. In this context, the increased role of teachers as human resources playing a crucial part in adopting and implementing AI technology in the classroom has become essential. The research method using a library research approach to analyze the training needs and development of teachers in facing the AI era. This research method is based on literature studies and analysis of relevant documents from sources such as scientific journals, books, and related research reports. The focus is on the impacts arising from the presence of AI in education and identifying the types of training that can be used to prepare and support educators in integrating AI technology into the learning process. The research indicates that the presence of AI has positive impacts on the education world, such as enhancing the effectiveness of learning, aiding teachers in finding in-depth materials, facilitating the creation of local curricula more effectively, and assisting higher education students in composing scientific articles. However, there are still negative impacts, such as students becoming dependent on AI and thus becoming lazy to study.There are various types of training that teachers can undergo to face AI, including Learning and Innovation Skills, Information, Media, and ICT Literacy, and TPACK.